Social Support from Academic Supervisor as a Driver of Academic Resilience: The Mediating Roles of Growth Mindset and Academic Self-Efficacy Among Students Who are Behind in Their Studies - Muhammad Hafiz Abiddiya; Rezki Hariko (Scidacplus, 2026)
Academic resilience is an essential psychological capacity that enables students to cope effectively with academic challenges, particularly those who experience delays in completing their studies. This study aimed to examine the direct and indirect relationships among supervisor social support, growth mindset, academic self-efficacy, and academic resilience among university students experiencing delayed study completion. A quantitative explanatory research design was employed involving 199 students from the Faculty of Sport Sciences, Universitas Negeri Padang, Indonesia. Data were collected using the Academic Resilience Scale (ARS-24), Academic Self-Efficacy Scale, Growth Mindset Scale, and Social Support Scale and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results showed that academic self-efficacy (β = 0.303, p < .001), growth mindset (β = 0.448, p < .001), and supervisor social support (β = 0.167, p = .011) had significant positive effects on academic resilience. Supervisor social support also had significant positive effects on growth mindset (β = 0.818, p < .001) and academic self-efficacy (β = 0.460, p < .001). Furthermore, growth mindset and academic self-efficacy significantly mediated the relationship between supervisor social support and academic resilience. The proposed structural model explained 76.7% of the variance in academic resilience, indicating substantial explanatory power. These findings underscore the importance of integrating internal psychological resources and external social support in promoting students’ academic resilience. The study provides empirical evidence for an integrated model of academic resilience and suggests that universities should strengthen academic supervision, counseling services, and psychological support programs that enhance growth mindset, academic self-efficacy, and supportive supervisor–student relationships to facilitate timely study completion.